Public knowledge of cardiopulmonary resuscitation in Republic of Slovenia - Rajapakse, Renata; Noč, Marko; Kersnik, Janko (Wiener Klinische Wochenschrift, 2010)
Summary AIM: In a case of cardiac arrest lay people in Republic of Slovenia rarely start basic life support procedures. The aim of this study was to determine the extent of knowledge about and attitude towards cardiopulmonary resuscitation in lay population. METHOD: A cross-sectional telephone survey using computer-assisted telephone interview method was performed in August and September 2006. Questionnaire contained sections regarding participant demographics, knowledge of cardiac arrest signs and of cardiopulmonary resuscitation procedures (CPR), previous courses of CPR training, and the awareness of emergency phone contact number. RESULTS: We interviewed 500 subjects. Nearly 70% of subjects had attended courses on CPR, but nearly 80% of them did so more than 10 years ago. Less than half of the subjects knew that CPR include rescue breathing (47%) and chest compressions (44.6%). Subjects who passed training on CPR knew that twice more often ( p < 0.001). Knowledge on resuscitation skills was generally poor. Only 1.2% knew the rate of chest compressions, 2.2% knew the correct compressions-to-ventilations ratio in adult CPR, and only 3 out of 500 subjects (0.6%) knew both. Correct site and correct strength for chest compressions were stated in 37.6 % and 13.0 %, respectively. Both the correct site and the correct strength were stated more often in CPR-trained group ( p = 0.002 and p = 0.02, respectively). CONCLUSION: Lay public in Republic of Slovenia has poor knowledge on CPR. Knowledge is better in trained versus untrained individuals. Educational campaign in the community would improve response to cardiac emergencies.